As condições do encarceramento na unidade prisional feminina do Crato/CE: um estudo das particularidades femininas à luz dos direitos humanos - Carvalho, Mariana Lacerda Cervantes de (2023)
This study is part of a dissertation in the Postgraduate Program in Human Rights, Citizenship and Public Policies at the Universidade Federal da Paraíba, whose objective is to reflect on the conditions of incarceration in the Women's Prison Unit in Crato, Ceará, based on a study of women's particularities from the perspective of Human Rights. More specifically, the study discusses female incarceration as a social and legal phenomenon, covering the effects of the origin of the imprisonment in the penitentiary system, and the Fundamental Rights provided by the national and international legal system, as well as criminological aspects of incarcerated women in Brazil; moreover, it describes the women's penitentiary system in the municipality of Crato, Ceará, focusing on analysis of physical structure of the penitentiary, on the effectiveness of incarcerated women rights, and on the existence of penitentiary and welfare policies; finally, the research investigates the conditions of women's incarceration in the Women's Prison Unit of Crato, Ceará, based on the medical records of these women in order to obtain sociodemographic and criminological information, as well as the reports obtained by prison staff for assistance and structural data and for public prison policies. Hypothetical and deductive method was used to develop the research, adopting quantitative and qualitative approaches divided into two stages: bibliographical research with documentary research and field research. For this purpose, medical records were analyzed for the entire female prison population during the period in which the research was conducted, resulting in a total of 100 documents, as well as observation in the prison and interviews with 6 employees from specific sectors, which consisted of 1 employee from the prison's management, education, prison officers, psychology, social assistance and nursing, which was an important stage as it provided contact with the women's prison. Data obtained in the survey was interpreted and analyzed using Laurence Bardin's (2016) content analysis technique; the results revealed that the majority of incarcerated women in this prison have a low level of schooling, brown skin color, and single marital status, which is similar to national data (SISDEPEN, 2022). From the criminological perspective, more than half of all women are deprived of their liberty as a result of drug trafficking, a crime which predominates in the scenario involving female incarceration in a natiowide level (SISDEPEN, 2022). Although there is assistance and positive actions in the penal facility investigated, there are relevant absences to attend to the particular needs of incarcerated women, which include aspects of maternity, health, and the structuring of this women's prison.